Makna Stance Expressions dalam Teks Jurnalistik Media Berita Detik dan Kompas pada Topik Perubahan Iklim di Indonesia: Analisis Linguistik Korpus - Muhammad Rahmat Alimuddin; Gusnawaty Gusnawaty; Andi Agus Salim (Pusat Studi Bahasa dan Publikasi Ilmiah, 2022)
This study aims to map the use and identify the meaning of stance expressions in Detik and Kompas media texts on the topic of climate change in Indonesia. This study uses a corpus linguistic method with a mixed type of research between quantitative research and qualitative research. Research data were collected using the data adaptation method with copy-paste techniques. There are two steps in the data analysis method. The first step is identification and data mapping with frequency and concordance analysis using AntConc corpus linguistic software, the second step is analysis of Ken Hyland's interactional function model. The results showed that there were six forms of lingual units and three forms of interactional function elements. The forms of lingual units found are nouns, verbs, adjectives, adverbs, particles, and phrases. Then the interactional function elements found are attitude markers, boosters, and hedges. The interactional self-mention function was not found in the data. The meaning expressed by the stance expressed by the media Detik and Kompas on the topic of climate change in Indonesia is to support various climate change efforts and both media are careful in presenting information about climate change in Indonesia. This is indicated by the high use of elements of the interactional hedges function in the corpus.